Listening to Dura Europos: An Experiment in Archaeological Image Sonification - Shawn Graham; Jaime Simons (Internet Archaeology, 2021)
We present an experiment in sonifying archival archaeological imagery to make the act of looking at photography strange and weird. The sounds produced will then arrest us and slow us down, and make apparent to us the different ways that archaeological vision is constructed to particular effect/affect. It makes us alive to what is hidden or elided in the image itself; in slowing down, listening/looking/moving at one, we are moved towards enchantment, and engage in a kind of digital hermeneutics that reveals more than what the lens may have captured.